Lactococcus lactis I7 isolated from traditional Italian cheese making: a biotechnological integrated platform - Alberto Alfano; Darshankumar Parecha; Alessandra Fusco; Vittoria Savio; Ida De Chiara; Lidia Muscariello; Giovanna Donnarumma; Chiara Schiraldi (BMC Biotechnology)
Abstract Background There is growing interest in newly isolated lactic acid bacteria from traditional sources. In this study, a Lactococcus lactis strain identified and isolated from natural whey starter cultures of cow milk for the production of artisanal cheeses was cultivated in optimized vegan grade medium to assess its growing ability and metabolic fingerprint. In fact, traditionally fermented dairy products are considered nutritionally complete and possibly functional to human health with a number of benefits not only to the gastro-intestinal tract but also in a systemic manner. Results In fed batch experiments, we achieved 14 g/L dry cell weight and 1.9∙1010 viable colony forming unit increasing the values of experiment threefold and twofold respect to the batch processes, respectively. Additionally, the lactic acid (LA) production was quantified, and a maximal concentration of 78 g/L was achieved, which is approximately five-fold corresponding to the batch experiment results. This is in agreement with kinetic modeling of LA inhibition studies that highlighted a halved growth rate (µ) at 35 ± 5 g/L of LA whilst the growth blockage occurred at about 80 g/L. The samples obtaining after ultrafiltration processes and tested on three different pathogens, Enterococcus faecalis, Salmonella enterica subsp. enterica serovar Typhimurium and enteroinvasive Escherichia coli, gave a reduction on viability by 6–9 log on average. Conclusion This paper focused its attention on optimization of fermentation conditions (in particular a vegan grade media using Design of Experiment approach) using fed-batch and microfiltration processes increasing the production of biomass and bioactive molecules, with respect to the batch processes. At the end of the fed-batch fermentation, a downstream process based on membranes was performed in order to obtain bioactive molecules that proved antimicrobial activity against intestinal/food spoilage pathogens.